Comité editorial/Página legal - 12 2, RMI (Medicina e Investigación Universidad Autónoma del Estado de México; Vol. 12 Núm. 2 (2024): Revista de Medicina e Investigación Universidad Autónoma del Estado de México, 2024)
Comite Editorial/Página Legal